REVISITING THE CONCEPT OF THE JAVANESE ISLAM: GENEALOGY, ACADEMIC REPRESENTATION, AND CULTURAL STRATEGY - Achmad Tohe (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2021)
This article aims to revisit the understanding of the concept of syncretic Javanese Islam, which scholars have much debated. From the genealogical search for the syncretic Javanese Islamic concept produced by missionaries and orientalists; mapping of the academic representations of Javanese Islam produced by recent scholars; up to an explanation of the theoretical approach used to discuss the concept of syncretism. Based on selected literature sources, the results show that the syncretic Javanese Islamic concept formulated by missionaries and orientalists tends to be highly theological due to the Christian framework used. They were especially concerned about the universality of religion, the evolution of civilization, the hierarchy of religions, and the purity of religious doctrine. Recent scholars also tend to have inherited this conception of Javanese Islam. They constantly debated the ‘true’ or the ‘purity’ of Javanese Islam, thus resulting in the two dominantly opposing views. The intensity of the cultural encounter and the necessity of syncretism requires a more robust theoretical approach to obtain a more precise understanding of syncretism.